Adverse cutaneous drug reaction - Nayak Surajit; Acharjya Basanti (Wolters Kluwer Medknow Publications, 2008)
In everyday clinical practice, almost all physicians come across many instances of suspected adverse cutaneous drug reactions (ACDR) in different forms. Although such cutaneous reactions are common, comprehensive information regarding their incidence, severity and ultimate health effects are often not available as many cases go unreported. It is also a fact that in the present world, almost everyday a new drug enters market; therefore, a chance of a new drug reaction manifesting somewhere in some form in any corner of world is unknown or unreported. Although many a times, presentation is too trivial and benign, the early identification of the condition and identifying the culprit drug and omit it at earliest holds the keystone in management and prevention of a more severe drug rash. Therefore, not only the dermatologists, but all practicing physicians should be familiar with these conditions to diagnose them early and to be prepared to handle them adequately. However, we all know it is most challenging and practically difficult when patient is on multiple medicines because of myriad clinical symptoms, poorly understood multiple mechanisms of drug-host interaction, relative paucity of laboratory testing that is available for any definitive and confirmatory drug-specific testing. Therefore, in practice, the diagnosis of ACDR is purely based on clinical judgment. In this discussion, we will be primarily focusing on pathomechanism and approach to reach a diagnosis, which is the vital pillar to manage any case of ACDR.